Effects of High‐Density Gradients on Wildland Fire Behavior in Coupled Atmosphere‐Fire Simulations. (25th November 2022) - Costes, Aurélien; Rodier, Quentin; Masson, Valéry; Lac, Christine; Rochoux, Mélanie C.
Abstract: Coupled atmosphere‐fire modeling is recognized as a relevant approach for the representation of the interaction between a wildland fire and local meteorology at landscape scales. The atmospheric model component used in the coupled system is based on several approximations, which are adopted for computational efficiency or physical processes representation, including the widely used anelastic approximation. The validity domain of the anelastic approximation may be questioned in the context of high‐resolution wildland fire modeling due to the large fire‐induced heat releases near the surface. This study aims to study this question with the MesoNH anelastic model coupled with the Blaze fire model. A compressible version of the MesoNH‐Blaze coupled model has been developed for comparison with the anelastic system. The FireFlux I experimental fire is used for this comparative study conducted at a 10‐m and a 25‐m horizontal atmospheric resolution. Results show significant anelastic/compressible differences at a 10‐m resolution on the physical processes occurring near the fire with higher horizontal velocities and the presence of gravity waves downstream of the fire. This is in addition to the fire plume with realistic larger vertical velocities. Differences at a 25‐m resolution are much smaller in all evaluated processes. The compressible system only enriches the physics underlying fire‐atmosphere interactions at a very high resolution, which means that the anelastic approximation remains relevant for large‐scale coupled atmosphere‐fire simulations, considering the significant economy concerning numerical costs. Plain Language Summary: Wildfires burn large amounts of forests each year, destroying the living habitat of many species, endangering human settlements and provoking cross‐continent smoke events leading to air quality issues. Wildfires result from complex physical, chemical and biological processes. Understanding the fundamental processes driving wildfire behavior is a key point for the prediction of fire spread across the landscape and the induced atmospheric dynamics. Numerical models coupling the atmospheric dynamics (wind, temperature, air density and pressure, etc.) and fire front evolution are efficient tools in this scientific process. This paper evaluates how such model simulations are affected by the way in which the effects of high air density gradients induced by the very large amount of heat released into the atmosphere are modeled. When the spatial resolution of the atmospheric model is as high as 10 m, an exact – compressible – formulation leads to the formation of gravity waves downstream of the fire, and to stronger fire‐induced wind, fire propagation and larger vertical velocities than an approximate (and computationally faster) approach. At a resolution of 25 m, which is still very high, the approximate approach leads to results, which are as good as the exact one. This can then be used to simulate wildland fire behavior at landscape‐to‐meteorological scales. It also paves the way for future accurate wildfire forecast systems. Key Points: A compressible version of the MesoNH atmospheric model has been developed to evaluate equation system approximations in wildfire simulation Horizontally buoyancy‐driven effects induce turbulent movements, waves ahead of the fire, and a bending of the plume The anelastic approximation for the atmosphere model is suitable to represent wildland fire effects, except for resolutions of 10 m or finer